Clinical Profile and Outcome of Children with Acute Central Nervous System (CNS) Infection from a Tertiary Care Centre in the Present Vaccination Era - B RAMESH BABU; P PUNITHA; ADITHYA VIJAYARAGHAVAN; A PRAKASH; J BALAJI (JCDR Research and Publications Pvt. Ltd., 2022)
Introduction: Meningitis is a common tropical infection which causes significant morbidity and mortality in children. Vaccination is available now-a-days for Haemophilus influenza and Pneumococcus which are the common infection causing meningitis. Profile of acute Central Nervous System (CNS) infection in children varies with time to time as it depends on the organism, age, seasonal period, outbreaks, immunisation and place. Aim: To study the clinical, microbiological, radiological profile and outcome of children with acute CNS infection in a tertiary care centre in the present vaccination era. Materials and Methods: This prospective observational study was done in the Department of Paediatrics, Government Dharmapuri Medical College Hospital, Tamil Nadu, India, from December 2018-June 2020. Fifty children from 1 month to 12 years with features of acute CNS infection were included in the study. Clinical features, CSF and serology findings, Computed Tomography (CT) scan findings and outcome were taken for analysis. The data were entered in Microsoft Excel software and analysed using Statistical Package for the Social Sciences (SPSS) Version 23.0. Results: During the study period, 50 children were diagnosed with acute CNS infection. A total of 37 (74%) children were less than 3 years and 31 (62%) male children were commonly affected. Fever 42 (84%), seizures 46 (92%) and altered sensorium 31 (62%) were the common symptoms. Status epilepticus 40 (87%), shock 18 (36%), respiratory distress 16 (32%) were common findings. In CSF, elevated cell count, reduced sugar, elevated protein were seen in 21 (42%), 14 (28%) and 27 (54%), respectively. Pneumococcus 3 (6%), Japanese Encephalitis (JE) 8 (16%), dengue 5 (10%), herpes 4 (8%), scrub typhus (aetiological agent Orientia tsutsugamushi) 2 (4%) were the common aetiological agents for CNS infection. CT brain was abnormal in 8 (16%) children. Nine children died (18%) and rest 41 (82%) recovered. Conclusion: In the present vaccination era, viruses and tropical fevers- JE, dengue, herpes and scrub typhus were common causes for acute CNS infection in children. Common clinical features were status epilepticus, fever, altered sensorium, respiratory distress and shock. Initial stabilisation of physiological status, specific management and JE vaccination are mandatory to improve the outcome in CNS infection.